INTERDYSCYPLINARNA SPECYFIKA KSZTAŁCENIA NAUCZYCIELI JĘZYKÓW OBCYCH (ZE SZCZEGÓLNYM UWZGLĘDNIENIEM PEDEUTOLOGII I GLOTTODYDAKTYKI) - Peć, Beata (Neofilolog, 2020)
The purpose of this paper is to present the interdisciplinary nature of foreign language teacher education both from a theoretical and empirical perspective - including findings from a research study which was conducted at the Institute of German Studies at the University of Warsaw. The article shows the diversity of approaches to teacher education and defines glottodidactics as the basic disciplines of foreign language teacher education, exposing the influence of these disciplines on each other. The article presents a sample interdisciplinary teacher training program and, based on the results of the author’s own research, the opinions of students on this subject.